BaZrO3 Photoluminescence Property: An Ab Initio Analysis of Structural Deformation and Symmetry Changes - Gurgel, Maria F. C.; Moreira, Mario L.; Paris, Elaine C.; Espinosa, Jose W. M.; Pizani, Paulo S.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Wiley-Blackwell, 2011)
This article reports a theoretical study based on experimental results for barium zirconate, BaZrO3 (BZ) thin films, using periodic mechanic quantum calculations to analyze the symmetry change in a structural order-disorder simulation. Four periodic models were simulated using CRYSTAL98 code to represent the ordered and disordered BZ structures. The results were analyzed in terms of the energy level diagrams and atomic orbital distributions to explain and understand the BZ photoluminescence properties (PL) at room temperature for the disordered structure based on structural deformation and symmetry changes. (C) 2009 Wiley Periodicals, Inc. Int J Quantum Chem 111: 694-701, 2011
Keywords: localized states; density functional theory; band structure; semiconductor; disordered solid